Structural Elements Energy Losses of Electrical Equipment due to a Violation of Symmetry of Power Transmission Mode Parameters - N. L. Novikov; R. A. Nechitaev; M. A. Kashin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The asymmetry of power transmission mode parameters due to the induction current effect on structural elements of electrical equipment is investigated. Three-phase AC current produces a rotating magnetic field that affects the power transmission system symmetry, and when it is violated, the induction current appears that causes additional heating of the electrical equipment. To find the flux linkage with research object caused by uncompensated magnetic field, a calculation was performed using the Poisson equation for vector magnetic potential. The symmetrical components method is used to calculate power losses in the asymmetric mode, taking into account losses in the ground. There is proposed a parametric synthesis of energy balance in structural elements of outdoors electrical equipment to calculate and verify the induction heating, taking into account the processes of natural convection, radiation and thermal conductivity. There are shown the thermograms of power transformer and gantry pillars on guy rods to open the additional energy losses caused by induction currents. Calculation of power transmission via overhead line taking into account the mutual induction of supporting structure was carried out in a three-phase vector system and in a transformed system using the symmetrical component method for the case of longitudinal asymmetry. Accounting the earth's resistance leads to a change in the ratio of active and reactive components, i.e. active power losses increase, and reactive ones become smaller, and, correspondingly, the load angle decreases. There are proposed the solutions in above examples to reduce additional energy losses and a technical and economic benefits for overhead line is performed. The result of the work can be useful in the design and modification of power transformers and overhead power transmission lines.